Beyond the Distributed Practice Effect: Is Distributed Learning Also Effective for Learning With Non-repeated Text Materials? - Greving, Carla Elisabeth; Richter, Tobias (Frontiers in Psychology, 2021)
Distributed learning is often recommended as a general learning strategy, but previous research has established its benefits mainly for learning with repeated materials. In two experiments, we investigated distributed learning with complementary text materials. SeventNinety-seven (Experiment 1) and 13060 (Experiment 2) seventh graders read two texts, massed vs. distributed, by one week (Experiment 1) or 15 min (Experiment 2). Learning outcomes were measured immediately and one week later and metacognitive judgments of learning were assessed. In Experiment 1, distributed learning was perceived as more difficult than massed learning. In both experiments, massed learning led to better outcomes immediately after learning but learning outcomes were lower after one week. No such decrease occurred for distributed learning, yielding similar outcomes for massed and distributed learning after one week. In sum, no benefits of distributed learning vs. massed learning were found, but distributed learning might lower the decrease in learning outcomes over time.